The role of outdoor sports activities in developing the psychological fitness of sixth-grade preparatory students - Obeid, L. Dr. Muhammad Hussein; Wadi, Asst. L. Alaa Ali; Obeid, Prof. Dr. Abbas Hussein (Sulaimani Journal for Humanities, 2026)
The study aimed to identify the level of psychological fitness among sixth-grade preparatory students and to determine the role of outdoor sports activities in developing their psychological fitness. The researchers adopted an experimental approach, as it was the most suitable method for achieving the research objectives. The research population consisted of sixth-grade science students in Al-Hashimiya district, Babil Governorate. The research sample was selected purposively from 120 students of Al-Murtada Secondary School for Boys, chosen for their cooperation in serving the research. These students were divided into two groups: a control group and an experimental group, each comprising 30 students. The research sample thus represented 50% of the original population. After reviewing a number of previous literature and studies, the researchers adopted the Psychological Fitness Scale prepared by (Al-Zamili, 2020). The scale consists of (42) items, distributed across six domains as follows: (7) items for the domain of self-confidence, (6) items for self-actualization, (4) items for psychological anxiety, (10) items for optimism, (5) items for courage, (5) items for social integration. Note that the answer alternatives according to the five-point Likert scale apply (very highly - highly - moderately - slightly - very slightly) with a correction key of (1, 2, 3, 4, 5). The scientific foundations were established, and the research instruments were then applied between November 20, 2021, and May 8, 2024. The research instruments were distributed to the students, who were asked to record the data in the designated spaces. Afterward, they were instructed on how to answer the items on each scale and given an example. They were informed that their answers would be confidential and would not be seen by anyone except the researchers. After collecting and statistically processing the data, a sample of students with a high level of psychological fitness was selected to participate in extracurricular sports activities. The sample was divided into two groups of one student each: the first experimental group participated in the outdoor sports activities, and the second group served as the control group. After extracting and statistically analyzing the data, the researchers concluded that there was a high level of psychological fitness among sixth-grade students, as measured by the psychological fitness scale, and that extracurricular activities had an effective impact on improving the psychological fitness of sixth-grade students. The researchers recommend conducting more extensive studies on other samples and considering the results of this study and the benefits of activating extracurricular activities. Its importance